Globalizing Religious Moderation: Indonesia’s Experience of Religious Moderation for the ASEAN and Global Contexts - Rahmat, Efendi; Solahudin, Dindin; Kusnawan, Aep; Azis, Rohmanur (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the potentials and challenges of globalizing Indonesia’s policy of religious moderation within the ASEAN and broader international context. Amid growing polarization rooted in religion, extremism, and identity-based conflicts, the Indonesian government—through the Ministry of Religious Affairs—has developed the religious moderation policy as both a normative and strategic framework to preserve harmony within plural societies. Using a qualitative approach based on case studies and document analysis, this research draws on primary data from official reports by the Ministry of Religious Affairs and secondary data from relevant international sources. The findings indicate that Indonesia’s model of religious moderation has begun to gain attention in regional and global forums, particularly through its integration into educational initiatives, interfaith dialogue platforms, and diplomatic arenas such as ICROM and KMBAAA. Nevertheless, several dysfunctions persist: resistance from ideological groups, elitist and symbolic implementation, inconsistency with ongoing domestic discrimination, and the ceremonial nature of international actor involvement. These findings underscore the urgent need for more inclusive, community-based, and consistent strategies if religious moderation is to evolve into a global value system. This study offers an original contribution by positioning Indonesia’s religious moderation not merely as a domestic policy, but as a transnational normative model relevant for diplomacy and religious studies.